Geopolitical discourse : where and what is Eurasia? - Rojnić, Dobrinka (Array, 2020)
Contemporary geopolitical discourses are to a large extent shaped by networks of global actors with different sources of power. In such networkskey source of power is not just a territory, but also effective and vibrant economic policies that are shaped by countries, companies and other economic actors. The growing attention on geopolitical and geostrategic issues have placed the issue of economic integration high on the list of policy and governance priorities in last two decades. While every country, region, alliance shapes its own geopolitical and geostrategic positioning by formulating and implementing its own energy policy, such policies are to a large extent influenced with what takes place in the territory of Eurasia. In geopolitical discourses, Eurasia has been in the focus of scholarly and political discussions for quite some time now. Previous reviews of geopolitical discourses on Eurasia have showed, however, that while the concept of Eurasia is often employed in the context of its relations with western democracies, the boundaries or properties of concept itself still remain unclear. This paper aims to tackle this problem and define Eurasia in geographical as well as cultural, political and social terms. The literature review and document analysis are, thus, employed to offer the answer to the question: “What and who is Eurasia?” While answering to the question, this paper takes into account the important role Eurasia plays for European Union as a territory with significant energy resources and with a consequential attractivity for economic integration with European Union and its members states. In order to offer the answer to the question “What and who is Eurasia?”, in order to unfold the dimensions of its geopolitical domination, the paper focuses on cultural, economic, geopolitical and social dimensions.